Genetic variants in the region harbouring IL2/IL21 associated with ulcerative colitis. Issue 6 (6th February 2009) - Festen, E A M; Goyette, P; Scott, R; Annese, V; Zhernakova, A; Lian, J; Lefèbvre, C; Brant, S R; Cho, J H; Silverberg, M S; Taylor, K D; de Jong, D J; et al.
Abstract : Objectives: Genetic susceptibility is known to play a large part in the predisposition to the inflammatory bowel diseases (IBDs) known as Crohn's disease (CD) and ulcerative colitis (UC). The IL2/IL21 locus on 4q27 is known to be a common risk locus for inflammatory disease (shown in coeliac disease, type 1 diabetes, rheumatoid arthritis, systemic lupus erythematosus and psoriasis), while the roles that interleukin 2 (IL2) and IL21 play in the immune response also make them attractive candidates for IBD. The objective of this study was to test for association between the IL2/IL21 locus and the IBDs. Methods: The four single nucleotide polymorphisms (SNPs) in the IL2/IL21 locus most associated with coeliac disease were genotyped in 1590 subjects with IBD and 929 controls from The Netherlands, and then replicated in a North American cohort (2387 cases and 1266 controls) and an Italian cohort (805 cases and 421 controls), yielding a total of 4782 cases (3194 UC, 1588 CD) and 2616 controls. Allelic association testing and a pooled analysis using a Cochran–Mantel–Haenszel test were performed. Results: All four SNPs were strongly associated with UC in all three cohorts and reached genome-wide significance in the pooled analysis (rs13151961 p = 1.35×10 −10, rs13119723 p = 8.60×10 −8, rs6840978 p = 3.07×10 −8, rs6822844 p = 2.77×10 −9 ). A moderate association with CD was also found in the pooled analysis (p value range 0.0016–9.86×10 −5 ). Conclusions: A strong association for the IL2/IL21 locus with UC was found, which also confirms it as a general susceptibility locus for inflammatory disease.